Hats, auctions and derandomization. Issue 3 (27th June 2013) - Ben‐Zwi, Oren; Newman, Ilan; Wolfovitz, Guy
Abstract We investigate derandomizations of digital good randomized auctions. We propose a general derandomization method which can be used to show that for every random auction there exists a deterministic auction having asymptotically the same revenue. In addition, we construct an explicit optimal deterministic auction for bi‐valued auctions. © 2013 Wiley Periodicals, Inc. Random Struct. Alg., 46, 478–493, 2015